Model pelatihan pemberdayaan sistem presensi digital berbasis kecerdasan buatan bagi siswa vokasi Cibening, Kabupaten Kuningan - Budi Herdiana; Azi Azmi Farizi; Eko Budi Setiawan; Taryana Suryana; Sutono (Universitas Sanata Dharma, 2026)
The education sector demands artificial intelligence technology to promote the advancement of academic governance applications and learning methods. An AI-powered digital attendance system is among the technological solutions planned for introduction in this community service initiative. To date, students and educational staff within vocational secondary schools, particularly in Cibening, have not fully acquired practical knowledge of how to utilize this technology. This gap has also created challenges in academic and instructional activities, as they often face inaccurate attendance records of students and teachers when reporting academic results. Therefore, providing training and support for the adoption of this digital attendance system is critically important for participants within this program's framework. The implementation method of this community program was carried out in stages, beginning with the delivery of instructional material, followed by system demonstrations, and culminating in hands-on practice. The training content was structured into three components: foundational knowledge, an introduction to the digital attendance system, and hardware-software training. The results indicate that students’ understanding of AI increased by 34%, while their practical skills improved by 36%. The achievements of this community program are expected to contribute positively to administrative governance and academic learning processes in vocational schools.